Human memory a reader - Shanks, David R. (Arnold, a member of the Hodder Headline Group, 1997)
This reader is a collection of articles focusing on human memory since the 1980s. The readings have been chosen to provide a broad and up-to-date reflection of the main issues currently occupying memory researchers, with an emphasis on theoretical problems.